100P Combination of intratumoural double-stranded RNA (dsRNA) BO-112 with systemic anti-PD-1 in patients with anti-PD-1 refractory cancer. (15th December 2019) - Marquez-Rodas, I; Longo, F; Aix, S Ponce; Jove, M; Rubio, B; Blanco, A Calles; Rodriguez-Ruiz, M E; Ponz-Sarvise, M; Castañon, E; Gajate, P; Sempere-Ortega, C; Jimenez-Aguilar, E; et al.
Abstract: Background: BO-112 is a dsRNA (poly I:C) formulated with polyethylenimine, that upon Intratumoral (IT) injection acts by activating TLR3, RIG-1 and MDA-5. This induces immunogenic cell death and potentiate systemic therapy with checkpoint inhibitors in animal models. In patients (pts), single-agent BO-112 IT increases necrosis, apoptosis and expression of pro-immune genes in solid cancers, with a manageable safety. 1 mg was the dose combined with anti-PD-1 in the current clinical trial (NCT02828098). Methods: BO-112 was combined with anti PD-1 in 28 pts with solid tumors primarily resistant to anti PD-1 (nivolumab or pembrolizumab). A lesion >1 cm amenable to IT injection was required. 28 pts were treated with 1 mg IT BO-112 qw x 2 or 3 doses before continuing the previous anti PD-1 combined with BO-112, until progression, limiting toxicity or up to 1y. Pre & post BO-112 biopsies from injected lesion were analysed. Response was first assessed by RECIST 1.1 at week 8-12. Results: BO-112 related AEs and biological effects at interim analysis are summarized in the table. The combination was well tolerated. No deaths were associated with BO-112. Of 18 evaluable pts for response, at first assessment: 2 have achieved an objective partial response (PR) (1 melanoma and 1 renal carcinoma), with 1 of them continuing treatment; 11 patients had stable disease (SD); 5 patients progressed (PD). Additionally 6 patients progressed prior to the first evaluation, 3 died before efficacy assessments and 1 received palliative radiotherapy and was considered not evaluable. Conclusion: BO-112 combined with anti PD-1 shows a manageable safety profile, direct antitumor effects and innate and adaptive immune system activation. Efficacy analyses suggest potential to reverse primary resistance to anti-PD1 treatment. Studies in other indications, including combination with radiotherapy, are planned. Clinical trial identification: NCT02828098. Legal entity responsible for the study: Bioncotech Therapeutics. Funding: Bioncotech Therapeutics. Disclosure: I. Marquez-Rodas: Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pierre Fabre; Advisory / Consultancy, Research grant / Funding (institution): Amgen; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bioncotech; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Regeneron; Advisory / Consultancy, Research grant / Funding (institution): Incyte; Non-remunerated activity/ies: Biosequence; Research grant / Funding (institution): Idera. P. Lopez-Casas: Full / Part-time employment: Bioncotech. M. Martin: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Puma; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen; Advisory / Consultancy: Tahio; Advisory / Consultancy: Pharmamar; Advisory / Consultancy: Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Speaker Bureau / Expert testimony: Daiichi. D. Tersago: Full / Part-time employment: Bioncotech. M. Quintero: Full / Part-time employment, Officer / Board of Directors: Bioncotech. I. Melero: Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution): Alligator; Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy: Merck-Serono; Advisory / Consultancy: Genentech; Advisory / Consultancy: Genmab; Advisory / Consultancy: Incyte; Advisory / Consultancy: Tusk; Advisory / Consultancy: Numab; Advisory / Consultancy: Molecular Partners; Advisory / Consultancy: F Star; Advisory / Consultancy: Bayer; Advisory / Consultancy: AstraZeneca. All other authors have declared no conflicts of interest.